Differences in the Time Course of Disease Progression, Quality of Life and Health Service Utilization in Women with Endometriosis. Issue 1 (January 2017) - Brandes, Iris; Hillemanns, Peter; Schippert, Cordula
Introduction: This study aimed to identify different subgroups (clusters) of patients (n = 182) based on the previously defined variables "age" and "diagnostic delay" in order to identify varying needs of (socio-)medical care. Methods: Five clusters were identified by two-step cluster analysis (SPSS 23.0). The mean values for parameters of quality of life, time course of disease progression and health service utilization were compared by chi-square and Kruskal-Wallis H test, and tested for correlations using Spearman's correlation coefficient. Results: Clusters I and II patients recognized their endometriosis symptoms at a relatively late age. The results showed a short diagnostic delay and a low subjective disease burden, although cluster I was characterized by a high level of fatigue. Cluster III results indicated that a lack of social support and comparatively long diagnostic delay were major problems in this group. The women in cluster IV had the worst quality-of-life scores and a below-average utilization of services. Statistical analysis showed a significant association between an early age of onset of endometriosis symptoms and a very long delay in diagnosis. These women perceived their menstrual symptoms as "normal" or as "hypochondria". Cluster V patients were mainly concerned about maintaining their work ability and employment. Conclusions: In gynecological practice, special attention should be given to the very young women, as the early onset of endometriosis symptoms and a long delay in diagnosis may indicate the risk of an unfavorable course of the patient's medical and socio-medical history over time.